Satisfacción y desempeño laboral de los docentes de administración de la facultad de ciencias económicas y de negocios, Iquitos 2022 - Montani Guevara, Salvador Valentino (2023)
This research aimed to determine the relation between job satisfaction and job performance of professors of administration at the Faculty of Economics and Business, Iquitos 2022. The type of quantitative approach research was used, the scope of the research will be correlational-descriptive. The research design will be non-experimental and transectional or cross-sectional. The sample will be the same as the population, that is, the 21 administration professors of the Faculty of Economics and Business, Iquitos 2022. A Pearson correlation value equal to 0.838** and a (bilateral) sigma value of 0.000 were obtained as a result, concluding that there is a significant relation between job satisfaction and job performance of administration professors at the Faculty of Economics and Business, Iquitos 2022. After analyzing the dimensions of variable 1 Satisfaction, it is confirmed that this variable has a "medium" level, since it has the highest percentage of 47.6% according to the responses, therefore it is necessary to carry out actions to improve. Regarding variable 2 Job Performance, it is possible to conclude that this variable has a "low" level, since it has the highest percentage of 47.6%, therefore it is urgent and necessary to carry out actions to improve.